Mathematics
CherieSevern
34

solve the equation for y

+3
(2) Answers
Georgey

2.)   8x - 4y = -12          Subtract 8x from both sides              -4y = -8x - 12   Divide both sides by -4                    y = 2x + 3          4.)         5x = -y + 6   Add y to both sides        5x + y = 6          Subrtract 5x from both sides                y = -5x + 6 6.)   -5y + 10x = 5             Subtract 10x from both sides                 -5y = -10x + 5   Divide both sides by -5                    y = 2x - 1

zvwilliams

5x= -y+6 add y to both sides 5x-y=6 Plug zero in for x to get Y. y=-6  Is this what is being asked or is it supposed to be like y=-5x+6 since you are stilling solving in terms of y.

Add answer